ANALISIS NILAI TAMBAH PENGELOLAAN LIMBAH PRODUKSI MEUBEL KAYU SEBAGAI PRODUK INOVATIF DI TIMIKA PAPUA - Muhammad Ihwan; Muh. Sabir (CV. ADIBA AISHA AMIRA, 2023)
This research aims to determine the added value of managing wooden furniture production waste as an innovative product in the city of Timika. The research method used is the descriptive research method, namely a method for examining the status of a group of people, an object, a set of conditions, a system of thought or a class of events in the present. In this research, the data collection methods used were the interview method, observation method, and documentation method. To determine the existence of a positive influence, the analytical instrument used in the research is analysis of the cost of production. The results of this research show that the cost of production for miniature bonsai is Rp. 35,490/unit and added value of Rp. 1,597,050, while the cost of production for briquettes is Rp. 9,793/kg and added value of Rp. 145,500.